Small Ruminant Lenti-virus infection in imported sheep in Greece - GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ), N. D.; DOVAS (Χ.Ι. ΔΟΒΑΣ), C. I.; CHATZINASIOU (E. ΧΑΤΖΗΝΑΣΙΟΥ), E.; BOUZALAS (Η. ΜΠΟΥΖΑΛΑΣ), I.; ARSENOS (Γ. ΑΡΣΕΝΟΣ), G.; PAPANASTASSOPOYLOU (Μ. ΠΑΠΑΝΑΣΤΑΣΣΟΠΟΥΛΟΥ), M. (Journal of the Hellenic Veterinary Medical Society, 2017)
During the last years, a large number of Assaf-E sheep have been brought into Greece from Spain. In total, 57 randomly selected Assaf-E sheep purchased from Spain to five 5 different farms in Greece were examined serologically on arrival for Small Ruminant Lentiviruses. Of these, 25 animals were found to be seropositive against Small Ruminant Lentiviruses. Taking into account the above findings, we suggest a more strict legislation at the sheep sales.